Influence of imidazolium based green solvents on volume phase transition temperature of crosslinked poly(N-isopropylacrylamide-co-acrylic acid) hydrogel. Issue 4 (12th December 2014) - Chang, Chi-Jung; Reddy, P. Madhusudhana; Hsieh, Shih-Rong; Huang, Hsin-Chun
Abstract : Ionic liquids, known as green solvents, can be used effectively to obtain the desired phase transition temperature for a given stimuli responsive polymeric material. Abstract : The volume phase transition temperature (VPTT) of crosslinked poly( N -isopropylacrylamide- co -acrylic acid) (PNIPAM- co -AA) hydrogel in water in the presence of five imidazolium based ionic liquids (ILs) was studied. The VPTT of PNIPAM- co -AA hydrogel can be modulated to different extents by the addition of different amounts of ILs. The modulations in VPTT values can be attributed to the IL-induced alterations in hydrophobic, hydrophilic and hydrogen bonding interactions of PNIPAM- co -AA hydrogel with the neighboring solvent and molecular chains. The influence of ILs having a common cation, 1-butyl-3-methylimidazolium cation ([Bmim]) and different anions, such as iodide (I − ), tetrafluoroborate (BF4 − ), chloride (Cl − ), acetate (CH3 COO − ) and hydrogen sulfate (HSO4 − ), on the phase transition of PNIPAM- co -AA hydrogel was monitored by the aid of differential scanning calorimetry (DSC), dynamic light scattering (DLS) and Fourier transform infrared (FT-IR) spectroscopy. Furthermore, the interfacial properties between aqueous IL and polymer surface were scrutinized with the help of contact angle (CA) measurements. The overall specific ranking of ILs in preserving the hydration layer around the PNIPAM- co -AA hydrogel in water was [Bmim][I] > [Bmim][BF4 ] > [Bmim][Cl] > [Bmim][Ac] > [Bmim][HSO4 ]. The trend of these ILs followed the well-known Hofmeister series. Interestingly, the PNIPAM- co -AA hydrogel in water shows abnormal salting-out property in the presence of [Bmim][BF4 ] at higher concentration and this abnormal behavior can be explained based on the lack of sufficient binding sites on the macromolecule for higher number of [Bmim][BF4 ] at a higher concentration.